Gravitating the Gig Economy for Reshaping the Careers Using Technological Platform in the Digital Age in an Emerging Economy - Mimi, Afsana; Mani, Lisa (Universitas Bina Darma, 2024)
The gig economy, driven by digital platforms and technological advancements, is reshaping traditional career pathways globally, particularly in emerging economies like Bangladesh. This study explores the gig economy's impact on career development, focusing on university students and graduates in Bangladesh. Using a mixed-methods approach, including surveys and interviews with 100 gig workers, the study reveals the motivating factors, challenges, and opportunities associated with gig work. The findings reveal that 56% of graduates in Bangladesh are involved in gig economy jobs, indicating a significant shift in career pathways. Among university students, 66% engage in gig work as an alternative income source before securing fixed positions. Furthermore, 61% of respondent’s view gig jobs as a means to gain experience quickly, which they believe will benefit their future careers. Freelancing emerges as the largest segment of the gig economy, encompassing 30% of gig workers. However, the study also highlights significant challenges, including social security issues and the lack of social and institutional recognition for gig workers. This study contributes to the theoretical understanding of the gig economy in developing countries, specifically in the South Asian context. Methodologically, it provides a holistic view of the gig economy's impact on career development. The research underscores the potential of the gig economy to alleviate unemployment and foster self-reliance among youth in Bangladesh.